Struktur dan Sifat Pelesapan dalam Cerita Rakyat Bali - Made Ratna Dian Aryani (Pusat Kajian Bali Universitas Udayana, 2021)
The focus of this article is about ellipsis that occurs in the discourse in the Balinese folklore. Ellipsis is a part of the cohesiveness of a discourse so that it becomes a complete discourse. The research method used is descriptive qualitative analysis. This study uses ellipsis theory from Halliday and Hasan which is supported by McCarthy's ellipsis deixis theory. The data source was taken from a collection of tales in the Balinese language, namely the book Pupulan Satua Bali II. The results of this study indicate that the ellipsis that occurs in the book of fairy tales is in the form of nominal ellipsis which refers to humans (people) in the conversation and story prologue, verbal ellipsis that occurs in fairy tale conversations, refers to lexical ellipsis in the verb word class, and the ellipsis of clauses because clauses are considered as expressions of speech functions, such as statements, questions, responses, and clauses that have a structural part consisting of core and propositional elements. Even though there is an ellipsis, the process of conveying the content and message of the story is still effective.